Perguruan Islamiyah sebagai Lembaga Pendidikan Islam Tertua di Pontianak - Dendy Ramadhan; Hariansyah Hariansyah; Wahab Wahab (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This article discusses an institution that has long existed and has a very important role in Pontianak. Beginning with the study conducted at the home of H. Arif until the establishment of an institution called “Islamic college.” Islamic educational institutions are institutions or places where the educational process takes place with the aim to change the behavior of individuals towards better through interaction with the surrounding environment. And the change in question is certainly based on Islamic values. This study uses a qualitative method with a narrative approach that narrates and interprets the role of an Islamic educational institution from its foundation. The research findings show that Islamic schools experience development and progress as Islamic education institutions in Pontianak and have challenges in dealing with invaders.